4CPS-286 Early impact of COVID on the activity of a clinical research oncology pharmacy unit at a tertiary care hospital. (14th March 2021) - Rovira Torres, P; Latorre García, P; Martinez Casanova, J; Esteban Sanchez, C; Serramontmany Morante, E; Garcia Ortega, P; Carreres Prieto, M; Maños Pujol, L; Cidoncha Muñoz, I
Abstract : Background and importance: The COVID-19 pandemic has impacted notably on clinical care and led to numerous challenges in the conduct of clinical trials (CT). Hospital pharmacies have had to develop new procedures and strategies to ensure pharmaceutical care, availability of treatment and patient safety. Aim and objectives: To analyse the activity in a clinical research oncology pharmacy unit during the COVID-19 period. Material and methods: We retrospectively collected the number of site initiation visits (SIV) and pharmaceutical care visits (screening visits, cycle 1 day 1 (C1D1) visits, follow-up visits, medical queries or patient's queries) performed in our unit from January to September 2020. Three phases were differentiated: 'pre-state of emergency' from 1 January to 13 March; 'state of emergency' from 14 March to 21 June; and 'post-state of emergency' from 22 June to 30 September. Results: During the 'pre-state of emergency' phase, 31 SIV and 273 pharmaceutical care visits were performed. Of these 273, 75 were screenings, 67 C1D1 visits, 26 follow-up visits, 28 medical queries and 77 patient queries. In the 'state of emergency' phase, 47 SIV and 206 pharmaceutical care visits were performed. Of these 206, 69 were screenings, 55 C1D1 visits, 10 follow-up visits, 35 medical queries and 37 patient queries. During the first 90 days of this emergency state, citizens were confined, so remote pharmaceutical care and remote SIV were implemented. 34 screenings were performed and 33 queries about interactions or drug instructions for patients were resolved. Medication was delivered to 139 patients. Four chemotherapy regimens were modified, extending in time administrations of pembrolizumab and cetuximab in four patients. 28 SIV were performed remotely (10 phase I CT, 7 phase II CT and 11 phase III CT). During the last phase, 60 SIV and 365 pharmaceutical care visits were performed. Of these 365, 83 were screenings, 79 C1D1 visits, 42 follow-up visits, 95 medical queries and 66 patient queries. Conclusion and relevance: The oncohaematological CT pharmacy unit managed to maintain pharmaceutical activity and care during the state of emergency period due to COVID-19, highlighting a considerable increase in activity in the months after the state of emergency. References and/or acknowledgements: Conflict of interest: No conflict of interest